Water loss and partitioning of the oil fraction of mushroom chips using ultrasound-assisted vacuum frying. (December 2020) - Devi, Shoma; Zhang, Min; Ju, Ronghua; Bhandari, Bhesh
Abstract: Sonication and microwave treatments for vacuum frying (VF) were studied to achieve the optimal frying conditions and improve the quality of fried products. Button mushrooms were used as a raw material. VF, microwave-assisted vacuum frying (MVF), ultrasound-assisted vacuum frying (UVF), and microwave combined with ultrasound VF (UMVF) techniques were used to produce the mushroom chips. Moisture content, oil partitioning coefficient (Kp), dielectric properties (DP), water activity (aw ), and temperature distribution of chips were measured and compared among different frying methods. The UMVF increased the moisture evaporation rate and reduced the oil content of chips compared to other treatments. The Kp of UMVF was 0.069, whereas, for UVF, MVF, and VF, it was 0.041, 0.050, and 0.034, respectively, indicating that sonication could reduce oil penetration into the product. Odor profile analysis using an e-nose suggested that the sonicated chips had the most acceptable flavor parameters. The treatments did not significantly affect the aw, which ranged from 0.58-0.37. Whereas, the DP were enhanced. The UMVF process was shown to be a viable technology that could be used for frying to obtain high-quality products.